2015
DOI: 10.1177/0954405415592120
|View full text |Cite
|
Sign up to set email alerts
|

New concept to aid efficient fibre integration into metal matrices during ultrasonic consolidation

Abstract: Ultrasonic consolidation has been shown to be a viable metal-matrix-based smart composite additive layer manufacturing process. Yet, high quantity fibre integration has presented the requirement for a method of accurate positioning and fibre protection to maintain the fibre layout during ultrasonic consolidation. This study presents a novel approach for fibre integration during ultrasonic consolidation: channels are manufactured by laser processing on an ultrasonically consolidated sample. At the same time, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Among the bonding techniques used for thermoplastic matrix composites, ultrasonic welding is very attractive for composite processing and joining, since it is characterized by a low-energy input, highly localized heating, very short welding times, and ease of automation [ 18 , 19 , 20 ]. During ultrasonic welding, the parts to be joined are held together under pressure and subjected to ultrasonic vibrations in the 20–40 kHz range [ 21 , 22 ]. The heat is produced at the joint interface through a combination of surface and intermolecular friction which leads to matrix melting.…”
Section: Introductionmentioning
confidence: 99%
“…Among the bonding techniques used for thermoplastic matrix composites, ultrasonic welding is very attractive for composite processing and joining, since it is characterized by a low-energy input, highly localized heating, very short welding times, and ease of automation [ 18 , 19 , 20 ]. During ultrasonic welding, the parts to be joined are held together under pressure and subjected to ultrasonic vibrations in the 20–40 kHz range [ 21 , 22 ]. The heat is produced at the joint interface through a combination of surface and intermolecular friction which leads to matrix melting.…”
Section: Introductionmentioning
confidence: 99%
“…This recrystallized joint interface is inherent in all UAM and ultrasonic metal welded joints to some degree. The group has continued to conduct low-power UAM research in various application areas, and in recent years, into integrating fibers (Monaghan et al , 2015; Masurtschak et al , 2017) and embedding electronics (Li et al , 2015; Li et al , 2017; Bournias-Varotsis et al , 2018).…”
Section: Low-power Uammentioning
confidence: 99%
“…80 mm by 25 mm) and then coating it with a layer of self-adhesive polyimide tape (75 μm thick Kapton™ tape). This aluminium substrate is commonly used with UAM [6][7][8]26] and the polyimide tape has excellent insulating, mechanical and thermal properties. The polyimide tape also provides an excellent surface for the dispensing of the conductive materials and past research has shown that it can withstand the mechanical loads introduced during UAM [10].…”
Section: Sample Preparation and Syringe Dispensingmentioning
confidence: 99%
“…This allowed researchers in the past to create composite metal matrix structures with embedded functional materials and other smart features, such as optical fibres [5,6], shape memory alloy fibres [7,8], other shape memory and magnetostrictive materials for embedded sensing applications [9] and smart switches for a structural antenna [10].…”
mentioning
confidence: 99%